Influence of growth temperature on SnO2 nanowires - Tiong, Teck Yaw; Yahaya, Muhammad; Dee, Chang Fu; Lim, Kean Pah; Yeop Majlis, Burhanuddin; Sow, Chorng Haur (W. S. Maney & Son, 2009)
Tin oxide (SnO2) nanowires have been synthesised using a thermal evaporation approach on quartz (SiO2) substrates in nitrogen atmosphere with a mixture of milled SnO2 powder and graphite as reactants. The substrates were placed vertically right above the reactants during the growth at 850, 900, 950 and 1000°C. A SnO2 thin film layer has been used as the nucleation site which is different from the conventional methods of using metal catalyst as seed for growth. SnO2 thin films have self-catalysed to form SnO2 nanowires at 950°C. At 850 and 900°C, plenty of SnO2 clusters landed on the substrates which were originated from the non-vaporised SnO2 powder. An optimum range of temperature was obtained for growth of clean SnO2 nanowires which were free from metal catalysts and non-vaporised SnO2 clusters.